2020
DOI: 10.1038/s41467-020-17088-6
|View full text |Cite
|
Sign up to set email alerts
|

Nampt-mediated spindle sizing secures a post-anaphase increase in spindle speed required for extreme asymmetry

Abstract: Meiotic divisions in oocytes are extremely asymmetric and require pre-and post-anaphaseonset phases of spindle migration. The latter induces membrane protrusion that is moulded around the spindle thereby reducing cytoplasmic loss. Here, we find that depleting the NAD biosynthetic enzyme, nicotinamide phosphoribosyl-transferase (Nampt), in mouse oocytes results in markedly longer spindles and compromises asymmetry. By analysing spindle speed in live oocytes, we identify a striking and transient acceleration aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 53 publications
(120 reference statements)
2
26
0
Order By: Relevance
“…53,58,59 Furthermore, reducing NAD þ levels through knockdown of the NAD þ synthetic enzyme, NAMPT, in oocytes compromised quality by impairing asymmetric division. 60 Thus, NAD þ has emerged as a pivotal node in the oocyte's aging process and constitutes a promising target for therapeutic approaches aimed at reversing poor quality.…”
Section: Prospects and Challenges For Diagnosing And Improving Poor Omentioning
confidence: 99%
“…53,58,59 Furthermore, reducing NAD þ levels through knockdown of the NAD þ synthetic enzyme, NAMPT, in oocytes compromised quality by impairing asymmetric division. 60 Thus, NAD þ has emerged as a pivotal node in the oocyte's aging process and constitutes a promising target for therapeutic approaches aimed at reversing poor quality.…”
Section: Prospects and Challenges For Diagnosing And Improving Poor Omentioning
confidence: 99%
“…In metaphase, spindle migrates from the center to the cortex, and in anaphase, the spindle continues to migrate outward to induce membrane protrusion required for extremely asymmetric division 25,27,28 . The failure of spindle migration in each phase destroys asymmetric splitting and produces larger PBs 21 . Interestingly, our results showed that DBDPE exposure damaged the migration of anaphase I spindle rather than the migration of metaphase I spindle (Figure 2, Figure S2).…”
Section: Discussionmentioning
confidence: 75%
“…25,27,28 The failure of spindle migration in each phase destroys asymmetric splitting and produces larger PBs. 21 Interestingly, our results showed that DBDPE exposure damaged the migration of anaphase I spindle rather than the migration of metaphase I spindle (Figure 2, Figure S2). Consistent with previous research, 25 DBDPE exposure led to the failure of anaphase I F I G U R E 5 DBDPE exposure inhibited the inactivation of CDK1 in oocytes at the onset of anaphase I.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…NAD + in turn regulates oxidative stress in oocytes at least in part via a family of NAD + -dependent deacetylases and deacylases known as sirtuins (SIRT1-7); oocytes from mice over-expressing SIRT2 exhibit delayed aging associated with reduced ROS ( Bertoldo et al, 2020 ), while deletion from oocytes of another sirtuin, SIRT1, results in increased oxidative stress that compromises embryonic development leading to early-onset female infertility ( Iljas et al, 2020 ). Interestingly, the importance of NAD + for oocyte quality extends beyond sirtuin-support roles as it is also critical for enabling oocytes to retain maximum cytoplasmic reserves during meiotic division ( Wei et al, 2020 ). It has also been found that expression of enzymes responsible for producing coenzyme Q10 (CoQ10), a major antioxidant and component of the mitochondrial electron transport chain, is reduced in oocytes from aged mouse and human oocytes ( Ben-Meir et al, 2015 ).…”
Section: Vulnerability Of Oocytes To Oxidative Stress and Dna Damage During Agingmentioning
confidence: 99%